2016
DOI: 10.1159/000447886
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Teriflunomide of Erythrocyte Cell Membrane Scrambling Following Energy Depletion, Oxidative Stress and Ionomycin

Abstract: Background/Aims: Teriflunomide, an inhibitor of pyrimidine synthesis and thus proliferation of activated T and B lymphocytes, is successfully used for treatment of inflammatory disease. Teriflunomide has further been shown to trigger apoptosis of tumor cells and has thus been considered for the treatment of malignancy. In analogy to apoptosis of nucleated cells, erythrocytes may enter suicidal death or eryptosis, which is characterized by cell shrinkage and phospholipid scrambling of the cell membrane with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 107 publications
2
11
0
Order By: Relevance
“…The effect is at least partially due to increase C-reactive protein, which increases cytosolic Ca 2+ activity and ceramide formation in erythrocytes. As several inhibitors of eryptosis are available [2-4, 93, 94], eryptosis and subsequent development of anemia may be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…The effect is at least partially due to increase C-reactive protein, which increases cytosolic Ca 2+ activity and ceramide formation in erythrocytes. As several inhibitors of eryptosis are available [2-4, 93, 94], eryptosis and subsequent development of anemia may be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that stimulated eryptosis may lead to anemia and thrombosis, it may be desirable to inhibit eryptosis. As a matter of fact, a wide variety of compounds such as blebbistatin, phlorhizin, vitamin C, resveratrol, reversine, hydroxytyrosol, volasertib, ASP3026 and teriflunomide have previously been shown to inhibit eryptosis in vitro . Some of these substances have previously been shown to counteract oxidative stress and may potentially be effective in vivo and could, therefore, be considered for the treatment of eryptosis‐induced anemia in different clinical conditions.…”
Section: Pharmacological Inhibition Of Oxidative Stress In Erythrocytmentioning
confidence: 99%
“… 29 , 31 Moreover, a study assessing the effect of TFN on eryptosis indicated that concentrations ranging from 3.7 to 37 µM TFN might compensate oxidative stress-mediated erythrocyte changes in vitro . 32 In rats, it has been shown that after one single injection of 10 µg/g TFN, approximately 2–4% of the blood concentration was found in the brain (~2.5–4.1 µM). 30 Although an extrapolation to the human reality is not exact, we could suppose in treated patients a TFN concentration within the nervous system of about 3–7 µM.…”
Section: Introductionmentioning
confidence: 99%